Management of acute appendicitis in the COVID era: A Case Study: Management of appendicitis during COVID-19 - Back, Francesca; George, Bruce (Journal of the Nuffield Department of Surgical Sciences, 2022)
Acute appendicitis is a common surgical presentation usually managed with laparoscopic appendicectomy. There has been long-standing debate as to whether conservative management of acute appendicitis could provide a superior alternative to surgical management. COVID-19 infection emerged in December 2019 and was labelled as a pandemic by the World Health Organisation in March 2020. Re-structuring as a result of the pandemic forced rapid changes in guidelines from recommending surgical management to advocating for medical management in all cases of uncomplicated acute appendicitis. Mr C had a delayed presentation of complicated acute appendicitis as a result of anxiety about being in a clinical environment during the pandemic. This was successfully managed with surgery and a 4-day inpatient stay. This case report evaluates the best approach for the treatment of acute appendicitis, evaluates whether a change in management was appropriate in the case of a pandemic and details how to avoid more cases of delayed and complex presentation as a result of COVID-19.